What are the appropriate mapping units for ecosystem service assessments? A systematic review - Jiake Shen; Chundi Chen; Yuncai Wang (Ecosystem Health and Sustainability, 2021)
Context: Without clear understanding of the units used for ecosystem service (ES) mapping, ES assessment accuracy and the practical application of ES knowledge will be hampered. Method: We systematically reviewed 106 studies over the past 11 years to explore the type, characteristic pattern and deficiencies of mapping units. Result: We proposed that ES mapping units can be categorized into minimal unit for assessing ESs using corresponding indicators and methods, and aggregated unit for analysis and application based on research objectives, and classified the mapping units into five common types. Of the 12 characterizing variables of ES mapping studies, some have been shown to introduce a difference in the selection of mapping units and to exhibit characteristic patterns. We also found that the accuracy of ES assessments based on minimal units was lacking, and aggregated units were insufficient to establish a link between ES knowledge and practice. Conclusion: Herein, we propose possible solutions such as the use of fine spatial resolution grids and the introduction of additional data beyond land cover as supplements to improve the assessment accuracy. To enhance the availability of the results for practice, aggregated units connected with urban planning units should be established at a spatial level suitable for urban management.